Masons, tricksters and cartographers : comparative studies in the sociology of scientific and indigenous knowledge - Turnbull, David, 1943- (Studies in the history of science, technology, and medicine., 2000)
In an eclectic and highly original study, Turnbull brings together traditions as diverse as cathedral building, Micronesian navigation, cartography and turbulence research. He argues that all our differing ways of producing knowledge - including science - are messy, spatial and local. Every culture has its own ways of assembling local knowledge, thereby creating space through the linking of people, practices and places. The spaces we inhabit and assemblages we work with are not as homogenous and coherent as our modernist perspectives have led us to believe - rather they are complex and hetero.